2022
DOI: 10.1155/2022/8906306
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Perioperative Nursing of Vitrectomy for Ocular Trauma under the Guidance of Ophthalmoscope

Abstract: To explore the perioperative nursing methods and clinical effects of vitrectomy under ophthalmoscope in the treatment of severe ocular rupture, this study reviews the clinical effects of vitrectomy in the treatment of severe ocular trauma in China, analyzes the perioperative nursing of vitrectomy for ocular trauma under the guidance of an ophthalmoscope, and analyzes the importance of stage I debridement and suture, the choice of operation time, and the advantages of vitrectomy and perioperative nursing care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%